2014
DOI: 10.1177/1465116514527179
|View full text |Cite
|
Sign up to set email alerts
|

Do electoral rules matter? Explaining national differences in women's representation in the European Parliament

Abstract: The European Parliament (EP) has one of the highest proportions of women in its ranks, with over a third in 2009. Although previous research has pointed to the use of proportional representation (PR) in European elections as 'friendlier' to women, few have looked at differences in the types of PR rules in use in each country. In this article, we argue that the conventional wisdom according to which institutional design-the choice of electoral rules-should shape the composition of the EP does not hold, and sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 97 publications
1
28
0
Order By: Relevance
“…While all EU countries are required to use a proportional electoral system to elect their MEPs, individual Member States are free to vary the openness of ballot structure. As past research indicates that the openness of ballot structure is likely to influence women's electoral chances (Fortin‐Rittberger & Rittberger ; Luhiste ), we control for the presence or absence of preference vote option, with the latter being the baseline category.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While all EU countries are required to use a proportional electoral system to elect their MEPs, individual Member States are free to vary the openness of ballot structure. As past research indicates that the openness of ballot structure is likely to influence women's electoral chances (Fortin‐Rittberger & Rittberger ; Luhiste ), we control for the presence or absence of preference vote option, with the latter being the baseline category.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research in this area, however, offers mixed findings as to the impact of electoral rules on women's numerical representation in the EP. While Fortin‐Rittberger and Rittberger () find that variations in electoral rules between EU Member States do not have a systematic impact on the number of women among all candidates, studies focusing on viable candidacy suggest that the use of closed‐list PR increases women's party‐determined viability and chances of being elected to the EP (Luhiste ).…”
Section: Women's Representation In the European Parliamentmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to their representation on party lists, women seem to be slightly more highly represented in the EP. For example, some data collected by Fortin‐Rittberger and Rittberger () illustrates that women constituted 28 per cent of candidates on party lists for the 2009 EP elections. This compares with a 34.45 per cent representational figure for the same parliament, implying that women are slightly more successful than men once nominated.…”
mentioning
confidence: 99%
“…Methodologically, many studies on political groups of the EP and on women in the EP have been quantitative analyses of roll call voting behaviour or of gender gaps in political attitudes (Cullen, , p. 485; see Fortin‐Rittberger and Rittberger, ; McEvoy, ; Raunio and Weber, ). For instance, Fortin‐Rittberger and Rittberger () study the candidate selection practices of 100 political parties across the EU and show that inclusiveness at an early stage is key to more gender balanced representation. Luhiste and Kenny, in turn, compiled a dataset of the backgrounds of more than 700 MEPs in the context of the 2014 EP elections and found that political parties were key determinants to women's electoral success with some pathways to power being very different for women than men (Lühiste and Kenny, ).…”
Section: Methodology and Research Materialsmentioning
confidence: 99%